2021
DOI: 10.1093/mnras/stab831
|View full text |Cite
|
Sign up to set email alerts
|

The optical properties of three Type II supernovae: 2014cx, 2014cy, and 2015cz

Abstract: We present the photometric and spectroscopic analysis of three Type II SNe: 2014cx, 2014cy and 2015cz. SN 2014cx is a conventional Type IIP with shallow slope (0.2 mag/50d) and an atypical short plateau (∼86 d). SNe 2014cy and 2015cz show relatively large decline rates (0.88 and 1.64 mag/50d, respectively) at early times before settling to the plateau phase, unlike the canonical Type IIP/L SN light curves. All of them are normal luminosity SN II with an absolute magnitude at mid-plateau of M$_{V,14cx}^{50}$ = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Studies of dust across a range of environments, from the SMC (Welty et al 2006(Welty et al , 2012 to the ISM of QSO host galaxies (Baron et al 2016), have likewise indicated that E(B −V ) values of 0.05 mag are associated with higher W r (Na I) than implied by Poznanski et al (2012). As the Poznanski et al (2012) relation is commonly invoked to estimate the reddening of both type I and II supernovae in combination with measurements of W r (Na I) in spectroscopy of these objects (e.g., Smith & Andrews 2020;Bruch et al 2021;Dastidar et al 2021), it is important to appreciate potential biases that may arise from this calibration (e.g., Phillips et al 2013). Moreover, given the wide range in stellar masses of our GOTOQ host galaxies, we suggest that our sample may better represent the varied dust and ISM properties of supernova host galaxies than those focused purely on the Milky Way, SMC, or QSO host systems.…”
Section: Relation Between W R and Dust Reddeningmentioning
confidence: 96%
“…Studies of dust across a range of environments, from the SMC (Welty et al 2006(Welty et al , 2012 to the ISM of QSO host galaxies (Baron et al 2016), have likewise indicated that E(B −V ) values of 0.05 mag are associated with higher W r (Na I) than implied by Poznanski et al (2012). As the Poznanski et al (2012) relation is commonly invoked to estimate the reddening of both type I and II supernovae in combination with measurements of W r (Na I) in spectroscopy of these objects (e.g., Smith & Andrews 2020;Bruch et al 2021;Dastidar et al 2021), it is important to appreciate potential biases that may arise from this calibration (e.g., Phillips et al 2013). Moreover, given the wide range in stellar masses of our GOTOQ host galaxies, we suggest that our sample may better represent the varied dust and ISM properties of supernova host galaxies than those focused purely on the Milky Way, SMC, or QSO host systems.…”
Section: Relation Between W R and Dust Reddeningmentioning
confidence: 96%